Integrating early stimulation and play at scale: study protocol for “MAHAY Mikolo”, a multi-arm cluster-randomized controlled trial - Emanuela Galasso; Lisy Ratsifandrihamanana; Ann M. Weber; Caitlin Hemlock; Mathilde Col; Maria Dieci; Norotiana Rakotomalala; Valerie Rambeloson; Lia C. H. Fernald (BMC Public Health, 2022)
Abstract Background Hundreds of millions of children living in poverty worldwide are not reaching their full, developmental potential. Programs to promote nurturing and responsive caregiving, such as those in which community health workers (CHWs) conduct home visits to support optimal early childhood development (ECD), have been effective in small trials, but have not achieved similar success at scale. This study will explore two approaches to scale-up: converting a home-visiting model to a group-based model; and integrating the ECD curriculum into an existing government program. The objectives of the study are to: 1) Measure how the integration of ECD activities affects time and task allocation of CHWs and CHW psychosocial wellbeing; 2) Examine how the integration of ECD activities affects caregiver-child dyad participation in standard health and nutrition activities; and 3) Explore how the availability of age-appropriate play materials at home affects caregiver-child dyad participation rates in a group-based ECD program. Methods We will randomize 75 communities in rural Madagascar into three arms: 1) [C], which is the status quo (community-based health and nutrition program); 2) [T], which is C + ECD group sessions [T]; and 3) [T +], which is T with the addition of an enhanced play materials package for home use. All children between 6–30 months old at the time of the intervention launch will be eligible to participate in group activities. The intervention will last 12 months and is comprised of fortnightly group sessions in which the CHWs provide caregiver-child dyads with information relating to ECD; CHWs will also include structured time for caregivers to practice the play and child stimulation activities they have learned. We will administer monthly surveys to measure CHW time use and task allocation, and we will leverage administrative data to measure caregiver-child dyad participation in the group sessions. Discussion The results from the trial will provide the evidence base required to implement an integrated package of nutrition, health and ECD promotion activities at scale in Madagascar, and findings may be relevant in other low-income countries. Trial registration This trial is registered on the AEA Social Science Registry (AEARCTR-0004704) on November 15, 2019 and on ClinicalTrials.gov (NCT05129696) on November 22, 2021.